Overcoming barriers in the use of artificial intelligence in point of care ultrasound - Roberto Vega; Masood Dehghan; Arun Nagdev; Brian Buchanan; Jeevesh Kapur; Jacob L. Jaremko; Dornoosh Zonoobi (npj Digital Medicine)
Abstract Point-of-care ultrasound is a portable, low-cost imaging technology focused on answering specific clinical questions in real time. Artificial intelligence amplifies its capabilities by aiding clinicians in the acquisition and interpretation of the images; however, there are growing concerns on its effectiveness and trustworthiness. Here, we address key issues such as population bias, explainability and training of artificial intelligence in this field and propose approaches to ensure clinical effectiveness.